Model Matematika Dinamika Kemiskinan Dengan Pengaruh Konsumsi Alkohol - isra miati; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2023)
The problem of poverty is a major development challenge at the global level. Many strategies are implemented to overcome this problem of poverty. However, in overcoming this problem a common problem emerged among poor families, namely related to alcohol consumption. As a result of consuming excessive alcohol will make individuals become alcohol dependent and alcoholics. The aim of this research is to be able to see a mathematical model and the analysis obtained. The method used in this research is descriptive method. Based on the analysis that has been done, one free fixed point is obtained. Next, the stability of the fixed point will be determined, which shows that the free fixed point is stable if γδ+γμ+μσ+μ^2+μ_1 σ+μ_1 δ+μ_1 μ>βσ+βδ+βμ. The simulation results for the free fixed point show that at a certain time the problem will disappear if the rate of individuals from the poor group who are not addicted to alcohol to poor alcohol addicts (β) is reduced and the rate of individuals in the poor group addicted to alcohol in rehabilitation (γ) is increased.